1999
DOI: 10.1074/jbc.274.47.33616
|View full text |Cite
|
Sign up to set email alerts
|

Actin and Phosphoinositide Binding by the ActA Protein of the Bacterial Pathogen Listeria monocytogenes

Abstract: The surface protein ActA of the pathogenic bacterium Listeria monocytogenes induces actin-driven movement of bacteria in the cytoplasm of infected host cells and serves as a model for actin-based motility in general. We generated and purified soluble recombinant fragments of ActA and assessed their ability to interact with the acidic phospholipids phosphatidylinositol 4,5-bisphosphate and phosphatidylinositol 3,4,5-trisphosphate, both implicated in the regulation of actin polymerization. Purified ActA consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
58
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 55 publications
13
58
1
Order By: Relevance
“…These results confirm the abnormally low sedimentation velocity of 2.6 S and low diffusion coefficient observed in analytical ultracentrifugation experiments which indicate an elongated monomeric ActA molecule, in correspondence to recently published data (42). DISCUSSION The surface protein ActA from L. monocytogenes efficiently interacts with components of the host cell actin polymerizing machinery (21,42,43) presumably by functionally mimicking mammalian proteins such as zyxin and vinculin (21). Both zyxin and vinculin harbor FP 4 motifs similar to those of ActA that are responsible for the recruitment of Ena/VASP proteins.…”
Section: Acta Contains Four Equivalent Moderately Strong Binding Sitsupporting
confidence: 80%
“…These results confirm the abnormally low sedimentation velocity of 2.6 S and low diffusion coefficient observed in analytical ultracentrifugation experiments which indicate an elongated monomeric ActA molecule, in correspondence to recently published data (42). DISCUSSION The surface protein ActA from L. monocytogenes efficiently interacts with components of the host cell actin polymerizing machinery (21,42,43) presumably by functionally mimicking mammalian proteins such as zyxin and vinculin (21). Both zyxin and vinculin harbor FP 4 motifs similar to those of ActA that are responsible for the recruitment of Ena/VASP proteins.…”
Section: Acta Contains Four Equivalent Moderately Strong Binding Sitsupporting
confidence: 80%
“…A similar effect is seen using ActA lacking the entire aminoterminal region (amino acids 31 to 262) (159). An ActA fragment that consists of amino acids 60 to 100 binds actin, as measured in the same pyrene-actin assay, and a glutathione S-transferase (GST) fusion to ActA amino acids 62 to 103 binds fluorescently labeled monomeric actin (28,195). Mutagenesis of charged residues to alanine within amino acids 60 to 66, 70 to 77, or 80 to 88 decreases the binding of the mutant ActA to monomeric actin (86a), indicating that the entire region between amino acids 60 and 88 is involved in binding to monomeric actin (86a).…”
Section: Regions Of Acta That Bind Monomeric Actinmentioning
confidence: 66%
“…ActA amino acids 30 to 263 fused to a linker and expressed on the bacterial surface mediate actin tail assembly in cytoplasmic extracts (86), which demonstrates that the region is sufficient for actin tail assembly. When ActA is purified and bound to beads, the same region of ActA polymerizes actin in cytoplasmic extracts (28).…”
Section: Regions Of Acta That Bind Monomeric Actinmentioning
confidence: 99%
“…The finding of a phosphoinositide binding site at amino acids 184 -202 on ActA suggested that this binding site could account for the ability of the bacterium to attract these phosphoinositides (9). It was proposed that the binding of PtdIns(4,5)P 2 by ActA might serve to deliver this phosphoinositide to the actin polymerization zone of Listeria and uncap actin filaments.…”
Section: Effects Of Reducing Phosphoinositide Levels On Listeria Intrmentioning
confidence: 99%
“…The bacterial surface protein ActA directly stimulates actin assembly, bypassing the receptor-mediated signal transduction pathways that induce actin filament formation during phagocytosis and chemotaxis (8). Curiously, ActA has a phosphoinositide binding site in the amino-terminal region that is located within amino acids 184 -202 (9,10), and binding of PtdIns(4,5)P 2 and PtdIns(3,4,5)P 3 causes a conformational change in the amino terminus of ActA. However, in vivo phosphoinositide localization studies have not been performed, and the physiological significance of the inositide binding site has not been examined.…”
mentioning
confidence: 99%